Demonetization and Its Effects in India - Garg, Anju (Journal of Commerce and Trade, 2017)
On 8 nov 2016 Indian Government had taken a bold decision of banning the circulation of 500 and 2000 notes. The Central Government was judicious well thought out and had taken a well implemented step. This a measure was taken for the Prime Minister to solve the problem of corruption, black money and counterfeit money. This study will help us to know about the positive nd negative effect of the demonetization. This study is based on secondary data like magazines, internet, research paper through some companies etc. and to analyse all the aspects of demonetization and calculate the worse and better effects of it on india. It also studies the demonetization in other countries and compare it with India. JEL Classification : A 10, E 41, E 42, E 52.